Small companies and regulatory tiering: a legal and economic analysis of Zambia's new regime - Phiri Christopher (Pretoria University Law Press, 2025)
In 2017, Zambia adopted a new Companies Act. The main purpose of the new Act is to promote the development of Zambia’s economy through efficient regulation of companies. This article focuses on the small companies regime that the new Act introduces. More specifically, the article explores the extent to which the new small companies regime is fit for purpose by conducting a comparative analysis of that regime with the United Kingdom’s (UK’s) small companies regime in light of relevant literature, particularly literature in the field of regulatory economics. Overall, the analysis suggests that Zambia’s small companies regime is largely inapt to achieving its intended purpose. The article’s main argument in this connection is threefold. First, the new Act is somewhat at odds with its intended purpose insofar as it requires small companies to appoint a secretary. Exempting small companies from this requirement, as does the UK Companies Act of 2006, could better serve the purpose of the new Act. Second, whilst the exemption of small companies from the requirement to appoint auditors may be desirable, the 50 per cent shareholding threshold required for shareholders to demand an audit could inhibit controlling shareholder accountability and thus undermine the purpose of the new Act. A lower threshold such as the one applicable under the UK Companies Act, that is to say, ten per cent, could better serve the purpose of the new Act. Third, the lack of any special treatment for small companies as such vis-à-vis bookkeeping and financial reporting requirements could undermine the purpose of the new Act. Imposing lighter bookkeeping and financial reporting requirements on small companies, as does the UK Companies Act, could better serve the purpose of the new Act.